Penerapan Akuntansi Zakat, Infak/Sedekah Berdasarkan PSAK 109 Pada Lembaga Amil Zakat Nasional Yakesma Medan - Debbi Chyntia Ovami (Management Studies and Entrepreneurship Journal (MSEJ), 2021)
This study aims to determine the application of zakat, infaq / alms accounting based on PSAK 109 at the LAZNAS Yakesma Medan. This type of research is qualitative. The subject of the study was the national amil zakat institution Yakesma Medan. The object of research used is the application of PSAK 109 on zakat accounting. infak/ alms. The data analysis technique used is descriptive qualitative. The results of the study that the application of accounting required by PSAK No. 109 includes recognition, measurement, presentation, and disclosure. In terms of recognition of measurement, and presentation of LAZNAS Yakesma Medan has implemented in accordance with PSAK NO.109, while in terms of disclosure LAZNAS Yakesma Medan has not fully disclosed. Keywords: Application of Zakat Accounting, Infaq / Alms, PSAK 109